The Multilingual Pragmatics of New Englishes: An Analysis of Question Tags in Nigerian English - Westphal, Michael (Frontiers in Communication, 2022)
This paper presents a variational pragmatic analysis of multilingual question tags in Nigerian English, combining a corpus-pragmatic analysis of the Nigerian component of the International Corpus of English with a survey study on the preferences and attitudes of Nigerian students toward different question tag forms. The corpus study highlights multilingual pragmatic variation in terms of form and function of variant as well as English and non-English (i.e. derived from indigenous Nigerian languages) invariant question tags in six text types: conversations, phonecalls, classroom lessons, broadcast discussions, broadcast interviews, and legal cross-examinations. Nigerian speakers combine a wide range of English and non-English invariant forms, whereas variant question tags only play a marginal role and are not characteristic of Nigerian English. Text type influences the overall frequency of question tags and – together with the pragmatic function – constrains the use of individual forms. The survey study shows diverging results as the participants generally prefer variant over invariant question tags and show a strong dispreference for indigenous Nigerian forms when speaking English. Nevertheless, their preferences for specific forms over others are guided by the communicative setting and requirements of a given situation. The students also hold most positive attitudes toward variant question tags, while non-English tags are rated less positively on items reflecting decency. However, all question tag forms are valued in terms expressiveness. Hence, Nigerian students’ dispositions toward multilingual question tag use are guided by a prescriptive ideology that is biased toward canonized English forms. While indigenous Nigerian forms are well integrated into question tag use, indicating a high degree of nativization of Nigerian English at a pragmatic level, acceptance for these local forms is lagging behind. In general methodological terms, the paper shows that question tags – or discourse pragmatic features in general – have high potential for studying multilingual variation in New Englishes. However, studies on the multilingual pragmatics of New Englishes need to consider the full range of multilingual forms, take into account variety-internal variation via text type, and should ideally also study the users’ perspectives.